Health Locus of Control and Perceived Levels of Depression, Anxiety, Stress Among Pakistani Female Breast Cancer Patient - Naz, Rubina; Ambreen , Saima (Pakistan Armed Forces Medical Journal, 2025)
Objective: To explore how psychological strengths of Health Locus of control influence to psychological distresses (depression, anxiety, stress) in breast cancer female patients.Study Design: Cross sectional study.Place and Duration of Study: Oncology Department, Shifa International Hospital, Islamabad Pakistan, from Mar 2021 to Feb 2022.Methodology: A non- probability sampling technique (purposive sampling) was used. A total sample of n = 115 breast cancer patients whose age range was from 28- 89 years. A biographical sheet that contains personal and disease information of patient, along with two indigenously adapted standardized scales were used: Multidimensional Health Locus of Control Form- C (Wallston, Stein, & Smith, 1994), and DASS-21 (Lovibond & Lovibond, 1995). To assess the construct under observation in current study.Results: Findings suggested that Internal Health Locus of Control (IHLoC) and Doctors HLoC (DHLoC) are significantly and negatively correlated with DASS (Depression, Anxiety, and Stress) p